Diagnostics of readiness of future junior specialists with medical education to professional self-development: ascertaining stage of pedagogical experiment - Solodovnyk, Olena (ScienceRise: Pedagogical Education, 2017)
The article elucidates the aspects of diagnostics of the output states of the formation of readiness of future junior specialists with medical education to the professional self-development; the analysis of the obtained results was carried out. There was substantiated the topicality of the formation of readiness of future junior specialists with medical education to the professional self-development in the process of professional training. The aim of the ascertaining stage of the pedagogical experiment of the formation of readiness of future junior specialists with medical education to the professional self-development in the process of professional training was elucidated, main principles and methods were established, general logic was determined. The ascertaining stage of the pedagogical experiment determined: the level of readiness to the professional self-development in practicing junior specialists with medical education; the level of erudition of graduates of medical colleges in the problem of professional self-development; the level of topicality and importance of the problem of professional elf-development of junior specialists with medical education; the level of readiness of teachers of clinical disciplines in medical colleges to the formation of readiness of future junior specialists to the professional self-development in the process of professional training. There were studied the possibilities and methods of the formation of readiness of future junior specialists with medical education to the professional self-development